Expression of MRP1 gene in acute leukemia - Mahjoubi, Frouzandeh; Golalipour, Masoud; Ghavamzadeh, Ardeshir; Alimoghaddam, Kamran (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: Overexpression of the multidrug resistance-associated protein 1 (MRP1) gene has been linked with resistance to chemotherapy in vitro, but little is known about its clinical impact on acute leukemia patients. Our aim was to investigate the possible association between MRP1 gene expression level and clinical outcomes among Iranian leukemia patients. DESIGN AND SETTING: This was an analytical cross-sectional study on patients referred to the Hematology, Oncology and Stem Cell Research Center, Sharyatee Public Hospital, whose diagnosis was acute myelogenous leukemia (AML) or acute lymphoblastic leukemia (ALL). All molecular work was performed at NIGEB (public institution). METHODS: To correlate with prognostic markers and the clinical outcome of acute leukemia, MRP1 gene expression was assessed in 35 AML cases and 17 ALL cases, using the quantitative real-time polymerase chain reaction and comparing this to the chemotherapy response type. RESULTS: Mean expression in AML patients in complete remission (0.032 ± 0.031) was significantly lower than in relapsed cases (0.422 ± 0.297). In contrast, no signifi cant difference in MRP1 mRNA level was observed between complete remission and relapsed ALL patients. There was a difference in MRP1 expression between patients with unfavorable and favorable cytogenetic prognosis (0.670 ± 0.074 and 0.028 ± 0.013, respectively). MRP1 expression in M5 was signifi cantly higher (p-value = 0.001) than in other subtypes. CONCLUSIONS: The fi ndings suggest that high MRP1 expression was associated with poor clinical outcome and was correlated with the M5 subtype and poor cytogenetic subgroups among AML patients but not among ALL patients.